RETRACTED: Methodology for automated assembly and delivery of products using mivar expert systems - Andreev Aleksandr; Kotsenko Anton; Kim Radmir; Aladin Dmitry; Varlamov Oleg (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001